Adenosine: Direct and Indirect Actions on Gastric Acid Secretion - Arin, Rosa M.; Gorostidi, Adriana; Navarro-Imaz, Hiart; Rueda, Yuri; Fresnedo, Olatz; Ochoa, Begoña (Frontiers in Physiology, 2017)
Composed by a molecule of adenine and a molecule of ribose, adenosine is a paradigm of recyclable nucleoside with a multiplicity of functions that occupies a privileged position in the metabolic and regulatory contexts. Adenosine is formed continuously in intracellular and extracellular locations of all tissues. Extracellular adenosine is a signaling molecule, able to modulate a vast range of physiologic responses in many cells and organs, including digestive organs. The adenosine A1, A2A, A2B and A3 receptors are P1 purinergic receptors, G protein-coupled proteins implicated in tissue protection. This review is focused on gastric acid secretion, a process centered on the parietal cell of the stomach, which contains large amounts of H+/K+-ATPase, the proton pump responsible for proton extrusion during acid secretion. Gastric acid secretion is regulated by an extensive collection of neural stimuli and endocrine and paracrine agents, which act either directly at membrane receptors of the parietal cell or indirectly through other regulatory cells of the gastric mucosa, as well as mechanic and chemic stimuli. In this review, after briefly introducing these points, we condense the current body of knowledge about the modulating action of adenosine on the pathophysiology of gastric acid secretion and update its significance based on recent findings in gastric mucosa and parietal cells in humans and animal models.